Perancangan Sistem Informasi Pelayanan Customer Berbasis Website Pada LKP SMART Bandar Sribhawono Lampung Timur - Qurrota Ayun Hariyanto Putra; Didi Rosiyadi; Nila Hardi (CV. Creative Tugu Pena, 2024)
The LKP SMART Bandar Sribhawono is a Course and Training Institution in the field of Non-Formal Education that provides skills, knowledge, and attitudes to the community. In this digital era, the need for information systems that facilitate interaction between companies and customers is increasing, especially in the service sector. This thesis designs and builds a web-based customer service information system for LKP SMART using the SDLC method Waterfall model, UML system modeling, CodeIgniter 4 framework, PHP programming language, and XAMPP for connection to the MySQL database. At the testing stage using the BlackBox Testing method to ensure the application is as expected. The result is a web-based customer service information system that meets the needs of LKP SMART in serving customers. The main features include registration and managementof customer data, which are expected to improve the efficiency and effectiveness of services and help manage customer relationships in a more organized manner.